Effectiveness of The Card Sort Method on Improving Reading Ability Initial Understanding Structure Text Indonesia Language Subject Procedures to Grade V Students of State Elementary School 060837 West Medan - Mevy Sitorus, Ruth; Sutikno; Rahmat Kartolo; Juni Arpah; Julia Rahmadani (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to analyze the effectiveness of the Card Sort method in improving reading ability of initial understanding of procedure text structure in grade V students of State Elementary School 060837, Medan Barat District, Medan City, Academic Year 2025-2026. The formulation of the problem in this study is: "Can the application of the Card Sort method improve the ability to read initial understanding of procedure text structure in students?" This study used the Classroom Action Research (CAR) method which was implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were fifth grade students who were selected purposively. Data were collected through tests, observations, and interviews, then analyzed descriptively quantitatively. The results of the study showed a significant increase in students' reading ability. In cycle I, 35% of students understood the contents of the procedural text, while 65% did not understand. After improvements were made in cycle II, the number of students who understood the contents of the text increased to 80%, while those who did not understand decreased to 20%. In addition, other indicators of success also increased, such as students' ability to mention and explain characters in the text increased from 55% in cycle I to 75% in cycle II. Students' ability to find the main idea also increased, from 65% in cycle I to 82% in cycle II. Thus, the results of this study prove that the Card Sort method is effective in improving the ability to read the initial understanding of the structure of procedural texts. Therefore, this method is recommended to be applied in Indonesian language learning to improve students' understanding of procedural textsv